THE USE OF PICTURE STRIP STORY POSTED IN INSTAGRAM FOR TEACHING DESCRIPTIVE TEXT WRITING - Nurhayati, Uray Dwiyanti Siska; Y, Y. Gatot Sutapa; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was conducted to find out whether or not the use of Picture Strip Story posted in Instagram increases students’ writing ability in descriptive text, especially about a person with Pre-Experimental Research design as the method. By clustering random sampling, it was XI AKL 3 class at SMK Negeri 1 Pontianak, with 25 students selected as the sample of the research. Based on the findings, it was found that the t-test score was 8.214. It was higher than the t-table, which was 2.064 at the degree of freedom (df) N-1 (25-1=24) = 0.05. The result of the effect size was 1.64, where the category was a strong effect. It was revealed that the Null Hypothesis (Ho) was rejected. This means that Alternative Hypothesis (Ha) which is the use of Picture Strip Story posted in Instagram increases the students’ writing ability in descriptive text was accepted. Therefore, this technique is recommended to be used in teaching writing descriptive text about a person, but also other topics such as animal and place. Keywords: Writing, Picture Strip Story, Descriptive Text, Instagram, Pre-Experimental Research